EFEKTIVITAS KEBIJAKAN RETRIBUSI PADA DINAS PENGELOLAAN PASAR KEBERSIHAN DAN PERTAMANAN DI KABUPATEN KEPULAUAN TALAUD - Panggulu, Yosua (JURNAL ADMINISTRASI PUBLIK, 2013)
ABSTRACT : Referring to the Law No. 32 of 2004 on Regional Government and the law No. 33 of 2004 on Fiscal Balance between the Central Government and the local Government the responsibility for every area to meet the needs of their respective regions. Law No. 33Tahun 2004 Local Taxes , Levies , Regional Wealth Management results were separated and Miscellaneous Revenue Legal areas . Revenue by source mentioned above the most potential and give input area is the largest in the cash taxes and levies .Based on Government Regulation No. 66 Year 2001 on Regional Retribution , Kepulauan Talaud district government imposed a Regional Regulation No. 04 Year 2011 about Retribution in optimizing revenue in Kepulauan Talaud District . One of the existing retributions , namely Market Service of retribution . And technical institutions or who runs the billing is Departement of Markets Management, Sanitation and Landscaping Kepulauan Talaud District . Issues to be addressed in this study how the effectiveness of policy implementation services levy market on Market Office , Cleaning and Landscaping in Kepulauan Talaud.This study used qualitative methods , this study aims to describe , analyze and determine the effectiveness of the policy market service charges . Results of research conducted through the collection of data obtained through observation and interviews based on the following indicators : ( 1 ) responsiveness , ( 2 ) development , and ( 3 ) Sufficiency . Based on the results of the study conclude that the policy of market services at the Department of Market Management , Sanitation and Landscaping Kepualauan Talaud is quite effective . Based on the conclusion of the study , it is suggested , Department of Market Management, Sanitation and Landscaping Kepulauan Talaud optimize any policies / programs that already exist and new ones will be implemented in order to optimize revenue retribution.Keywords : Effectiveness, Optimize Revenue Retribution, Implemented And Policy Of Retribution.